Modelling Whitewater Park Hydraulics and Fish Habitat in Colorado. (15th July 2015) - Kolden, E.; Fox, B. D.; Bledsoe, B. P.; Kondratieff, M. C.
Abstract: Whitewater parks (WWPs) are increasingly popular recreational amenities, but the effects of WWPs on fish habitat and passage are poorly understood. This study investigated the use of a two‐dimensional (2‐D) model as compared with a three‐dimensional (3‐D) hydrodynamic model (flow ‐3D ® ) for assessing effects of WWPs on fish habitat. The primary aims of this study were to (1) examine the utility of 3‐D modelling versus 2‐D modelling in a hydraulically complex WWP and (2) compare modelled habitat quality for resident fishes with actual fish abundance and biomass generated from field sampling surveys. Two reaches of a wadeable river in Colorado were modelled: a natural reach and a reach containing a WWP. A 2‐D habitat suitability analysis for juvenile and adult brown trout, juvenile and adult rainbow trout, longnose dace and longnose sucker predicted the same or higher habitat quality in the WWPs than the natural pools for all four species and for all modelled flow rates; however, results from fish sampling found significantly higher fish biomass for all four species in natural pools compared with WWP pools. All hydraulic metrics (depth, depth‐averaged velocity, turbulent kinetic energy, 2‐D and 3‐D vorticity) had higher magnitudes in WWP pools than in natural pools. In the WWP pools, 3‐D model results described the spatial distribution of flow characteristics or the magnitude of variables better than 2‐D results. This supports the use of 3‐D modelling for complex flows found in WWPs, but improved understanding of linkages between fish habitat quality and 3‐D hydraulic descriptors is needed. Copyright © 2015 John Wiley & Sons, Ltd.